An evaluation of the subspecies Acris crepitans blanchardi (Anura, Hylidae) - Mccallum, Malcolm L.; Trauth, Stanley E. (Zootaxa, 2006)
We investigated the validity and distribution of the subspecies Acris crepitans blanchardi.  Currently Acris crepitans contains three subspecies: the northern cricket frog (A. c. crepitans), Blanchards cricket frog (A. c. blanchardi) and the coastal cricket frog (A. c. paludicola).  We examined the diagnostic characters of 1441 specimens from the center of the range (Arkansas, Missouri, and Mississippi), 161 specimens from the extreme northwest portion of this species range (South Dakota and Nebraska), and 85 from the extreme southeast portion of the species range (Florida and Georgia).  Discriminate analysis was applied to the tabulated data and no significant differences between portions of the range could be discerned.  No concrete evidence was found to support designation of specimens from South Dakota and Nebraska or from Smallens Cave (origin of the type specimen) as A. c. blanchardi.  This information places the subspecies A. c. blanchardi in a status of doubtful validity suggesting that no delineation between A. c. blanchardi and A. c. crepitans should be made at this time.